A semantic interoperability framework for software as a service systems in cloud computing environments / Reza Rezaei - Reza, Rezaei (2014)

(untitled)
In cloud computing environments, one of the most important barriers to the adoption of software as a service systems is interoperability. Generally, in cloud computing environments at software as a service level, interoperability refers to the ability of software as a service systems on one cloud provider to communicate with software as a service systems on another cloud provider. The current software as a service systems in cloud computing environments have not been built with interoperability as a primary concern. Software as a service systems in cloud computing environments are poorly developed to meet the interoperability challenges. A common tactic for enabling interoperability is the use of an interoperability framework or model. During the past few years, at software as a service level, various interoperability frameworks and models have been developed to provide interoperability between systems. The syntactic interoperability of software as a service systems have already been intensively researched. However, not enough consideration has been given to semantic interoperability issues. Both syntactic and semantic interoperability are necessary prerequisites to achieve interoperability. Achieving semantic interoperability is a challenge within the world of software as a service in cloud computing environments. Therefore, a semantic interoperability framework for software as a service systems in cloud computing environments is needed. In this thesis, we develop a semantic interoperability framework for software as a service systems in cloud computing environments. For this purpose, we illustrate how current technologies, such as service oriented architecture, can represent an adequate foundation for implementing such framework. The capabilities and value of service oriented architecture for semantic interoperability between software as a service systems in cloud computing environments will be studied and demonstrated. iv In order to evaluate the effectiveness of the proposed semantic interoperability framework for software as a service systems in cloud computing environments, extensive experimentation and statistical analysis have been performed. Overall, the effectiveness of semantic interoperability of software as a service systems in cloud computing environments with the proposed framework shows a significant improvement in comparison with the existing models and frameworks.